2021
DOI: 10.1200/jco.2020.39.28_suppl.203
|View full text |Cite
|
Sign up to set email alerts
|

Range, effectiveness, and implementation of decision aids supporting cancer survivors’ decisions over health services participation in the post-treatment phase: A systematic review.

Abstract: 203 Background: Cancer patients and survivors encounter a myriad of complex medical decisions starting from their diagnosis of cancer. However, current decision aids (DAs) largely focused on acute treatment and fertility decisions, and not on health service-related decisions such as adoption of supportive care services and programs targeting risk factor modification. This systematic review aims to identify and describe DAs supporting health service-related decisions after the completion of primary treatment u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…While available evidence demonstrated favourable outcomes of DA usage in increasing knowledge, reducing decisional conflicts, and enhancing satisfaction for cancer-related decisions [ 15 17 ], there was a disproportionate focus on screening and treatment decisions. A recent systematic review focusing on health services or care modality decisions after primary cancer treatment identified a Dutch study that examined DA usage for breast cancer follow-up care intensity in hospitals [ 18 ]. The study showed promising results in improving shared decision-making and reducing cost [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…While available evidence demonstrated favourable outcomes of DA usage in increasing knowledge, reducing decisional conflicts, and enhancing satisfaction for cancer-related decisions [ 15 17 ], there was a disproportionate focus on screening and treatment decisions. A recent systematic review focusing on health services or care modality decisions after primary cancer treatment identified a Dutch study that examined DA usage for breast cancer follow-up care intensity in hospitals [ 18 ]. The study showed promising results in improving shared decision-making and reducing cost [ 19 ].…”
Section: Introductionmentioning
confidence: 99%